PENERAPAN EVIDENCE BASED NURSING TERAPI DISTRAKSI AUDIOVISUAL MENONTON VIDEO KARTUN TERHADAP PENURUNAN TINGKAT KECEMASAN AKIBAT HOSPITALISASI PADA ANAK USIA PRASEKOLAH - Faradilla Azzahra (2023)
Anxiety in preschool children due to hospitalization is a condition of not fulfilling emotional needs to the fullest. The purpose of writing this scientific paper is to provide an overview of nursing care for preschool children who experience anxiety due to hospitalization and the application of audiovisual distraction therapy watching cartoon videos to overcome anxiety problems. Audiovisual distraction therapy is a process of diverting distracting attention to other stimuli through more attention-grabbing video and audio media. The number of respondents involved in this study amounted to 2 people, each of whom was given the same intervention. Anxiety scores were measured using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Audiovisual distraction therapy is watching cartoon videos once a day for 10-20 minutes along with other measures. The implementation was carried out for three days and it was found that there was an effect of audiovisual distraction therapy watching cartoon videos on reducing the level of hospitalization anxiety in preschool children